Comparative analysis on the financial performance of Islamic and conventional banks in Malaysia - Ahmed Sulub, Yasin; Che Mohd Salleh, Marhanum (International Research Centre of Islamic Economics and Finance (IRCIEF), 2018)
Islamic banks (IBs) are characterized by their uniqueness of complying with Shariah where the aim is to bring benefits to all parties. For that reason, previous research argued that these banks were stable in the aftermath of the recent global financial crisis unlike Conventional banks (CBs). Therefore, this paper aimed at comparing the financial performance of IBs and CBs, measured by Return on Equity (ROE), Return on Assets (ROA), Earnings per Share (EPS) and Debt Ratio. To examine this objective, the study chose four full-fledged IBs and four CBs in the period from 2012 to 2016 using t-test and correlation analysis. The findings revealed that CBs were more profitable and less leveraged than IBs. This research has implications for IBs that they should further improve their performance to become more competitive in the current financial industry. More importantly, the IBs need to uphold the Islamic ethics throughout the business to ensure both worldly and hereafter objectives is achieved. Future research should involve bigger samples and more performance indicators, either quantitative or qualitative, in order to extend the current research findings.